2008
DOI: 10.1080/10934520701781160
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicities of polyquaterniums and their associated polyelectrolyte-surfactant aggregates (PSA) to Gambusia holbrooki

Abstract: The toxicity of 11 polyquaterniums used in cosmetic applications, and polydimethyldiallylammonium chloride (poly(DADMAC)) were studied for toxicity of the polyquaternium alone, and of a polyquaternium/anionic surfactant complex as occurs in some cosmetic formulations. The surfactant used in the study was sodium dodecyl sulfate (SDS), which is used in cosmetic formulations under its International Nomenclature of Cosmetic Ingredients (INCI) name Sodium Laurel Sulfate. In fish immobilization studies with Gambusia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Recent findings suggest that common polyquaternium polymers are toxic to eastern mosquitofish, with EC50 values of approximately 1 mg L -1 . 8 These EC50 values are comparable to that of cetylpyridinium chloride, which is known to be toxic to fish, invertebrates, algae, and rats. 9,10 Moreover, Monte Carlo simulations of the efficiency a municipal wastewater treatment plants predict a removal rate of polyquaternium polymers commonly contained in cosmetics of less than 25%, which suggests that concentrations attained in the environment could be problematic.…”
Section: Introductionmentioning
confidence: 80%
“…Recent findings suggest that common polyquaternium polymers are toxic to eastern mosquitofish, with EC50 values of approximately 1 mg L -1 . 8 These EC50 values are comparable to that of cetylpyridinium chloride, which is known to be toxic to fish, invertebrates, algae, and rats. 9,10 Moreover, Monte Carlo simulations of the efficiency a municipal wastewater treatment plants predict a removal rate of polyquaternium polymers commonly contained in cosmetics of less than 25%, which suggests that concentrations attained in the environment could be problematic.…”
Section: Introductionmentioning
confidence: 80%
“…Some early work by Tooby et al (1975) found that the toxicity of polyquaterniums could be similar to that of cationic surfactants that are very toxic to fish, invertebrates and algae (Madsen et al 2001). Recent work by Cumming et al (2008) with a wider range of polyquaterniums has confirmed this finding and polyquaterniums of cosmetic origin have been included as 'chemicals of concern' in wastewater treatment plant (WWTP) effluent by Water Quality Research Australia (formerly known as the Cooperative Research Centre for Water Quality and Treatment) (Cumming 2007).…”
mentioning
confidence: 84%
“…Based on the few identified data, PQ-7 (4,300-5,200 kDa, 1.6 meq/g) has a low fish toxicity (LC 50 : 10-100 mg/L [154]). For PQ-10, LC 50 and EC 50 values for loss of equilibrium range from 0.96 mg/L to > 100 mg/L [66,155]. Chronic fish toxicity data were only available for PQ-6 (MW n.i.).…”
Section: Aquatic Organismsmentioning
confidence: 99%